ANALISIS PENDAPATAN DAN RISIKO USAHATANI KRISAN DENGAN SISTEM GREENHOUSE DI KECAMATAN TUTUR KABUPATEN PASURUAN MENGGUNAKAN METODE KOEFISIEN VARIASI - Hana Safira Hidayat; Teguh Soedarto; Sri Widayanti (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
East Java Province is one of the largest chrysanthemum flower production centers in Indonesia, with productivity increasing significantly in the 2019-2023 period, supported by ideal climate conditions and soil fertility. The objectives of this study are to: (1) analyze the profitability of chrysanthemum farming with a greenhouse system, (2) analyze the risks of production, prices, and income of chrysanthemum farming with a greenhouse system in Tutur District, Pasuruan Regency, (3) Determine the efforts made by farmers to overcome risks. The sample of this study were chrysanthemum farmers who planted using greenhouses in Tutur District, Pasuruan. The number of respondent farmers in this study was 53 farmers. Data analysis used a descriptive analysis approach and risk analysis (coefficient of variation). From the results of this study, information was obtained that the feasibility level of chrysanthemum farming had an R/C ratio of 1.15 with a total income of Rp238,240,475/Ha/planting season. The results of the risk analysis showed CV values of 0.20 for production; 0.09 for price; and 0.23 for income, respectively. This indicates higher fluctuations in production and income compared to price fluctuations. This higher income risk is due to post-harvest damage and dependence on local markets or middlemen. However, each risk has a CV <0.5, indicating that this farming business is generally profitable.